World Englishes as an Explorative Experience in Listening Classroom: Students’ Recognize, Preference, and Motivation - Armelia Nungki Nurbani (Universitas Islam Lamongan, 2022)
Teaching English as a foreign language (TEFL) has broadened around the world and involved the speakers from various countries. As the effect, teaching English using World Englishes is salient. The study aimed to explore the first year of English Education Department students’ perspectives toward teaching listening using World Englishes. This study used qualitative research with a singular snapshot case study. The audio of listening utilized different accents from three different circle such as American and British (inner circle), Indian (outer circle), Japanese and Indonesian (expanding circle). The data were taken from six English Education Department students that were in the first year. The data were collected by focus group discussion, interview, and observation. The data were analysed using thematic analysis. The result of the study revealed that the students were thrilled about listening using World Englishes. However, the students got difficulty in understanding some accents like British and Indian. It was also found that audio from Indonesian accents was the students’ favorite beside American. Moreover, the students were motivated in listening using World Englishes.